Defected ground structure-based wideband circularly polarized 4-port MIMO antenna for future Wi-Fi 6E applications - Yousef, Basma M.; Ameen, Allam M.; Desai, Arpan; Hsu, Heng-Tung; Dhasarathan, Vigneswaran; Ibrahim, Ahmed A. (International journal of electronics and communications, 2023)
A circularly-polarized (CP) wideband 4-port Multi-input multi-output (MIMO) antenna is proposed. The novel contribution of the proposed work lies in achieving CP through an L-shaped feedline and a carefully engineered orthogonally placed slotted ground plane geometry leading to a defected ground structure (DGS). A single-fed CP antenna structure is then converted to the 4-port MIMO antenna that achieves higher isolation due to polarization diversity. The MIMO antenna demonstrated an impedance bandwidth (IBW) spanning 65.01 % (from 3.81 GHz to 7.48 GHz), along with an axial ratio bandwidth (ARBW) of 20.10 % (from 5.47 GHz to 6.70 GHz). The 4-port CP MIMO antenna shows decent MIMO diversity performance. The measured results of the fabricated structure displayed good agreement with the simulated results. Antenna having both MIMO capability and circular polarization helps in reducing the multipath fading effect while increasing the latency. Thus, the proposed antenna having a wide overlapping Axial Ratio (AR) and Impedance Bandwidth (IBW) can be a very good choice for future devices using the Wireless Fidelity (Wi-Fi) 6E band.